セメント質骨性異形成症を合併した上下顎多発単純性骨囊胞の1例 - 吉村, 周作; 丹沢, 秀樹; 鵜澤, 一弘; 高原, 利和; 伊豫田, 学; 武内, 新 (日本口腔外科学会雑誌, 2019)
Simple bone cyst (SBC) is a lesion characterized by a bone cavity with a clear boundary without an epithelial lining. SBC often occurs in long bones, such as the humerus and femur, but is relatively rare in the maxillofacial regions. A 40-year-old woman was referred to our department because of a radiolucent region of the lower jaw observed on dental examination. In our department, X-ray examination revealed multiple cysts in the maxilla and mandible. Biopsy of one cyst of the left mandibular first molar region was indicated a diagnosis of SBC. Curettage of all cysts was performed in August 2017. Histopathological examination revealed no epithelial lining in the cyst. Moreover, the interior of the cystic cavity was hollow. A fibro-osseous lesion was found on the left maxillary cyst wall without an epithelial lining. It was finally diagnosed as an SBC with cemento-osseous dysplasia (COD). In recent years, simple bone cysts involving cemento-osseous dysplasia have been reported to recurrence. One year postoperatively, there has been no sign of recurrence, yet complete follow-up is imperative in the future.